Efficacy of Brazilian Propolis against Herpes Simplex Virus Type 1 Infection in Mice and Their Modes of Antiherpetic Efficacies. (14th June 2011) - Shimizu, Tomomi; Takeshita, Youhei; Takamori, Yasushi; Kai, Hisahiro; Sawamura, Rie; Yoshida, Hiroki; Watanabe, Wataru; Tsutsumi, Atsuko; Park, Yong Kun; Yasukawa, Ken; Matsuno, Koji; Shiraki, Kimiyasu; et al.
Abstract : Ethanol extracts (AF-06, 07, and 08, 10 mg/kg) of Brazilian propolis were administered orally to cutaneously herpes simplex virus type 1 (HSV-1)-infected mice three times daily on days 0 to 6 after infection to evaluate their efficacies against HSV-1 infection and significantly limited development of herpetic skin lesions. AF-07 and 08 significantly reduced virus titers in brain and/or skin on day 4 without toxicity, but AF-08 had no anti-HSV-1 activity in vitro . AF-06 and 08 significantly enhanced delayed-type hypersensitivity (DTH) to inactivated HSV-1 antigen in infected mice. Oral AF-08-administration significantly augmented interferon (IFN)- γ production by HSV-1 antigen from splenocytes of HSV-1-infected mice, while direct exposure of splenocytes of infected mice to AF-06 significantly elevated IFN- γ production in vitro . Thus, AF-08 might have components that are active in vivo even after oral administration and those of AF-06 might be active only in vitro . Because DTH is a major host defense for intradermal HSV-1 infection, augmentation of DTH response by AF-06 or 08, directly or indirectly, respectively, may contribute to their efficacies against HSV-1 infection. In addition, AF-06 and 07 possibly contain anti-HSV-1 components contributing to their efficacies. Such biological activities of Brazilian propolis may be useful to analyze its pharmacological actions.